The Method of Classifying Words through Questions - NERSISYAN, BAGRAT (Bulletin of Yerevan University B: Philology, 2021)
In this article, we are trying to present to a wide circle of researchers the method of classifying parts of speech, which in the eighties within the limits of one article was proposed by A. E. Khachatryan (A. E. Khachatryan, Classification of Parts of Speech through Questions, Bulletin of Yerevan University, 1986, No. 3, pp. 56-65). A. Khachatryan quite logically asserts and convinces us that adverbs should rightfully take their place next to nouns, adjectives, numerals, and verbs as they have a conceptual meaning and answer the corresponding questions: these are words indicating time, place, the manner of action, measure and degree. Thus, all parts of the speech answer the corresponding questions: what? what kind of? how much? what to do? when? where? how? how many times? (to what degree? to what extent?). The definition of parts of speech without considering the conceptual meaning will be empirical. With the help of interrogative pronouns, the corresponding lexical and grammatical categories of words are formed. The proposed classification logicallyreflects the semantic differentiation of parts of speech. In typological studies, it possible to compare adequate language units, to identify their similarities and differences, to determine language universals by this method, which is very important for linguistics. This method is logical, and therefore simple, so it can be used in schools and universities.